Gene–Environment Interaction: Small Deletions (DELs) and Transcriptomic Profiles in Non-Melanoma Skin Cancer (NMSC) and Potential Implications for Therapy - Farzana Jasmine; Armando Almazan; Yuliia Khamkevych; Maria Argos; Mohammad Shahriar; Tariqul Islam; Christopher R. Shea; Habibul Ahsan; Muhammad G. Kibriya (Cells)
Arsenic (As) is a risk factor for non-melanoma skin cancer (NMSC). From a six-year follow-up study on 7000 adults exposed to As, we reported the associations of single-nucleotide variation in tumor tissue and gene expression. Here, we identify the associations of small deletions (DELs) and transcriptomic profiles in NMSC. Comparing the (a) NMSC tissue (n = 32) and corresponding blood samples from each patient, and (b) an independent set of non-lesional, healthy skin (n = 16) and paired blood, we identified NMSC-associated DELs. Differential expressions of certain gene pathways (TGF-β signaling pathway, IL-17 pathway, PD-L1 pathway, etc.) showed significant interactions with these somatic DELs and As exposure. In low-As-exposure cases, the DELs in APC were associated with the up-regulation of inflamed T-Cell-associated genes by a fold change (FC) of 8.9 (95% CI 4.5–17.6), compared to 5.7 (95% CI 2.9–10.8) without APC DELs; in high-As-exposure cases, the APC DELs were associated with an FC of 5.8 (95% CI 3.5–9.8) compared to 1.2 (95% CI −1.3 to 1.8) without APC DELs. We report, for the first time, the significant associations of somatic DELs (many in STR regions) in NMSC tissue and As exposure with many dysregulated gene pathways. These findings may help in selecting groups of patients for potential targeted therapy like PD-L1 inhibitors, IL-17 inhibitors, and TGF-β inhibitors in the future.